Direct and indirect ways of managing epistemic asymmetries when eliciting memories. (April 2019) - Williams, Val; Webb, Joe; Dowling, Sandra; Gall, Marina
This article aims to explore how epistemic status is negotiated during talk about the life memories of one speaker. Direct questions which foreground 'remembering' can lead to troubled sequences of talk. However, interlocutors sometimes frame their first parts as 'co-rememberings', and the sequential positioning of these can be crucial to the outcome of the talk. We draw on almost 10 hours of video data from dementia settings, where memory is a talked-about matter. Our focus is on 30 sequences which are initiated with a question or other first part taking a K-stance, selecting one person as next speaker, and topically relating to the recipient's past life. We show how type 2 knowables can be used alongside markers of tentativeness, to jointly construct the recipient's epistemic primacy.